Odontogenic myxofibroma resembling dentigerous cyst - Ghazali, Ahmad Badruddin; Arayasantiparb, Raweewan (2019)
Odontogenic myxoma is a rare benign odontogenic tumor with an infiltrative local growth. It has a variety of radiographic appearances. A case of odontogenic myxoma on the mandible in a 44-year-old female was discovered accidentally. A panoramic radiograph revealed a well-defined unilocular radiolucency with corticated border associated with the unerupted right mandibular third molar resembling a dentigerous cyst. Cone beam computed tomographic images demonstrated the inferior alveolar canal displaced inferiorly, No bone expansion both buccal and lingual aspects, and no root resorption. The histopathological biopsy confirmed the diagnosis of odontogenic myxofibroma. Enucleation of the lesion with removal of the third molar was done. A follow-up radiographic examination at six months after operation showed no signs of tumor recurrence.